AB0882 Acute Rheumatic Fever: A Ever Present Disease in The Western World with Possible Insidious Invalidating Heart Involvement. (15th July 2016) - Pieropan, S.; Degani, D.; Picassi, S.; Dal Forno, I.; Caldonazzi, F.; Piacentini, G.; Boner, A.; Biasi, D.; Adami, S.; Prioli, M.A.
Abstract : Background: Rheumatic Fever (RF) is a systemic inflammatory disease following pharyngeal infection by goup A beta–hemolytic Streptococcus (GAS). Objectives: to describe the characteristics of rheumatic Fever in a pediatric population of Verona between the 2005–2015. Methods: Clinical presentation of 44 patients with diagnosis of Rheumatic Fever was investigated. Patient age, sex, age at diagnosis as well as Jones criteria fulfilled were reported. The presence/absence of familiarity of Rheumatic Fever, therapy prescibed, pophylaxis' adhesion and primary cardiac involvement with it's evolution after therapy were evaluated. Results: Incidence of RF in Verona is increasing according to our data Age at diagnosis ranged from 2 to 17 years old (mean age 9-+4 years). Among Jones criteria carditis is most frequently encountered and its severity is not correlated with the values of antistreptolysin o titer (ASO). Heart murmur Was present in 57% of cases at diagnosis. 2 cases had a grade 1 AV blockade and two children underwent pacemaker implantation due to complete not reversibile AV blockade; no case of pericarditis was diagnosed and valvular involment (according to WHF classification) included mitral rigugitation (46, 5%), aortic rigurgitation (7%) and bivalvular aortic-mitral rigurgitation (46.5%). Conclusions: RF has not disappeared in the western world; cardiac involvement, which is not correlated with the absolute value of ASO, is the most worrysome clinical condition due to its possible severe sequaela; regular cardiac US and EKG togetherwith thorough physical examination should always be performed in order to identify subclincal cases. While prompt high dose steroids and NSAIDS administration prevent severe evolutions, antibiotics rappresent the main instrument in the primary and secondary prevention of the chronic reumatic Heart disease.Individual susceptabilty is a point of concern for the outbrake of RF as well as the need to identify "rheumatic" streptococci in order to elaborate a specific vaccination. Disclosure of Interest: None declared